Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 14 (iii) Defective sight is very commonly found in inspections under the school Medical Service. In 1934, 9½ per cent. of the children examined had poor eyes. This is undoubtedly partly the result of the life in dark homes, where daylight is excluded by the tenements across the narrow street, and electric light is not installed. V. — SLUMS AND OVERCROWDING. (1) Examples of Existing Slums. In spite of municipal housing estates which were built with the aid of Exchequer subsidies between the wars, in spite of slum clearance and the drive against overcrowding, appalling conditions continue to exist in every town and in many rural areas as well. Here is a typical case recorded by Mr. Rowntree in his social survey of York : The house consists of four small rooms, and is occupied by 6 persons: "The pointing of the external walls is defective, and the roof is sagging and in poor condition, with loose tiles. The eaves gutters are defective at the joints, and in a rotted condition. There is no fall pipe at the front of the house. The house is verminous All the plaster is decayed and broken, the walls are damp and the doors and window frames are rotted. In the bedrooms and on the landing the floor boards are holed and loose and the joints weak. The stair treads are badly worn and there is no hand rail."* All surveys taken of our towns reveal similar conditions. A survey of conditions in Shoreditch in 1938 revealed that two-thirds of the families surveyed could never bath, unless they went out to the public baths ; and that 22 per cent. of these families shared a water closet with three or more households and 3 per cent. with four or more. Of 125 families, drawn from all parts of London, surveyed in the New Survey of London Life and Labour (1934), two out of five were without kitchen accommodation. (2) Overcrowding To-day. According to the New London Survey, 20 per cent. of the population was living at the rate of more than 2 per room, and 3 per cent. at the rate of more than 3 persons. By the low official standard of the Ministry of Health Overcrowding Survey in 1936, 3.8 of all the dwellings surveyed (covering 99 per cent. of the population) were overcrowded. The worst conditions were in Scotland ; a survey of all houses of rateable value not exceeding £43 showed that 23½ per cent. were overcrowded. Glasgow alone had 73,000 families overcrowded.* Next came London, with 70,000 families. At the outbreak of war two out of every three families in London were sharing a house. * Facts for Socialists, page 30. 15X/2/98/13